2017
DOI: 10.3892/etm.2017.4478
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic pregnancy in the liver incidentally diagnosed by imaging: A case report

Abstract: Abstract. The present report describes the case of a 31-year-old woman diagnosed with an ectopic pregnancy in the liver. The patient presented with amenorrhea for 40 days and abdominal distention for 27 days. A liver mass had been detected 6 days prior to presentation. Using ultrasound (US), a hyperechoic mass with a fluid sonolucent area was detected in the right hepatic lobe. Examination by computed tomography (CT) revealed the presence of a mass in the right hepatic lobe with a slightly low-density peripher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Very rarely does it occur in the cervix, and less-reported sites are the ovaries and broad ligaments. 3 , 4 This abnormal localisation of pregnancy is a life-threatening obstetrical condition found in women of reproductive age, and it is a leading cause of maternal death when rupture occurs in the first trimester of pregnancy. 5 , 6 , 7 , 8 The aetiology of EP is not well understood, but risk factors associated with EP include pelvic inflammatory disease, puerperal sepsis, previous termination of pregnancy, post-abortion sepsis, appendicitis and use of intrauterine contraceptive devices.…”
Section: Introductionmentioning
confidence: 99%
“…Very rarely does it occur in the cervix, and less-reported sites are the ovaries and broad ligaments. 3 , 4 This abnormal localisation of pregnancy is a life-threatening obstetrical condition found in women of reproductive age, and it is a leading cause of maternal death when rupture occurs in the first trimester of pregnancy. 5 , 6 , 7 , 8 The aetiology of EP is not well understood, but risk factors associated with EP include pelvic inflammatory disease, puerperal sepsis, previous termination of pregnancy, post-abortion sepsis, appendicitis and use of intrauterine contraceptive devices.…”
Section: Introductionmentioning
confidence: 99%
“…It is one of the major complications encountered during the first trimester of pregnancy, and it has been reported that 1.3–2.4% of all pregnancies are ectopic pregnancies [ 6 ]. Most ectopic pregnancies occur in women in the age-group of 30–40 years and tubal pregnancy is the most common type of ectopic pregnancy [ 8 , 14 – 17 ]. Ectopic pregnancy may occur in the ovaries, abdominal cavity, broad ligament, and cervix; however, these are rare sites of ectopic pregnancy [ 7 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The same technique with intravenous contrast enhancement showed a peripheral portion with a greatly increased density in the arterial phase and slightly increased density in the venous phase. A nonenhanced lower-density was evident in the central portion (9,21,29,33,40).…”
Section: Figurementioning
confidence: 97%
“…No history of pelvic inflammatory disease or uterine or tubal abnormalities at surgery were reported. An intrauterine contraceptive device was described to be in place in only two cases (40,42); in another case, the device had been removed before conception (4).…”
Section: Review Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation